Phylogenomic Insights into the Phylogeography of Halophila baillonii Asch. - van Dijk, Kor-jent (2023)
A molecular genetic approach was used to elucidate the phylogeographic relationships of the clover grass (Halophila baillonii Asch.) from three key regions within its current distributional range. Halophila baillonii is a small seagrass that has historically been only found in a few locations in the Caribbean and Atlantic coast of Brazil. In the past few decades H. baillonii has also been observed in the Eastern Tropical Pacific (ETP). Very little is known about the relationship between the ETP populations and the Caribbean and Atlantic ones. To study their relationship, we used a hybrid capture approach targeting chloroplast loci on samples from Belize, Brazil, and the Pacific coast of Costa Rica. Phylogenetic analyses resolved H. baillonii as monophyletic and placed the samples from Belize and Costa Rica in a clade sister to the Brazilian ones. The results clearly indicate that the ETP samples are very closely related to Belize and that the most likely explanation of its occurrence in the ETP is a recent introduction, possibly as a consequence of the opening of the Panama Canal.